2014
DOI: 10.1590/s0100-736x2014000100012
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P-glycoprotein, multidrug resistance-associated protein, glutathione-S-transferase pi and p53 in canine transmissible venereal tumor

Abstract: Pesq. Vet. Bras. 34(1):71-78, janeiro 2014 71 RESUMO.-[Expressão da glicoproteína-P, proteína associada à múltiplas drogas, glutationa-S-transferase pi e p53 no tumor venéreo transmissível canino.] A superexpressão das proteínas glicoproteína-P (Gp-P), proteína associada à resistência à múltiplas drogas 1 (MRP1) e p53 mutante e a enzima glutationa-S-transferase pi (GSTpi) está relacionada com resistência à quimioterapia em neoplasias humanas e caninas. Este estudo avaliou a expressão, por meio da imuno-hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
2
8
0
4
Order By: Relevance
“…The progressive increase of TVTs with high percentages of aggressiveness and variable response to chemotherapy, including resistance, is partially due to the high expression of p‐glycoprotein (Pgp) by tumour cells, which leads to the expulsion of chemotherapeutic . Thus, treatment cost increases, as do side effects such as anorexia, nephrotoxicity and myelosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…The progressive increase of TVTs with high percentages of aggressiveness and variable response to chemotherapy, including resistance, is partially due to the high expression of p‐glycoprotein (Pgp) by tumour cells, which leads to the expulsion of chemotherapeutic . Thus, treatment cost increases, as do side effects such as anorexia, nephrotoxicity and myelosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…Também exibiram reatividade as amostras de cólon canino, sem alterações patológicas, que foram utilizados como controle positivo das reações, e todas as amostras dos animais do grupo controle. Embora estes clones tenham sido concebidos para uso em humanos e animais de laboratório, tecidos caninos também são reativos, como visto neste estudo e nos de Ginn (1996) e de Gerardi et al (2014).…”
Section: Resultados E Discussaounclassified
“…8720-01) e anti-MRP1 (clone MRP1-Novocastra Laboratories Ltd, Newcastle, UK, Cód. NCL-MRP1) utilizados na imuno-histoquímica foram produzidos em camundongos contra antígenos humanos e seguiu-se a metodologia descrita por Gerardi et al (2014) com algumas modificações. A expressão da MRP1 e gp-P foram pesquisados em cortes de 3 m de espessura montados em lâminas pré-tratadas com Poly-L-lisina (Cód.…”
Section: Methodsunclassified
“…A fourth possible proposed mechanism may involve overexpression of the some chemotherapy resistance enzymes in transmissible tumors [24,25]. It has been reported that P-glycoprotein (P-gp) the efflux pump, and glutathione-S-transferase (GSTpi) which is associated with multidrug resistance of tumor cells and are involved in drug detoxification and control of apoptosis were significantly overexpressed in canine transmissible venereal tumor mainly at cytoplasm and nuclei and both of these proteins are associated with multidrug resistance to chemotherapy in neoplasms [25][26][27].…”
Section: Possible Mechanisms On Devil Extinctionmentioning
confidence: 99%
“…It has been reported that P-glycoprotein (P-gp) the efflux pump, and glutathione-S-transferase (GSTpi) which is associated with multidrug resistance of tumor cells and are involved in drug detoxification and control of apoptosis were significantly overexpressed in canine transmissible venereal tumor mainly at cytoplasm and nuclei and both of these proteins are associated with multidrug resistance to chemotherapy in neoplasms [25][26][27]. Telomerase is up-regulated in Tasmanian devil cancer cells but not in normal tissues.…”
Section: Possible Mechanisms On Devil Extinctionmentioning
confidence: 99%